Domestic wastewater biosolids accumulation by liquid state bioconversion process for rapid composting - Fakhru'l-Razi, A.; Alam, Md. Zahangir; Idris, Azni; Abd-Aziz, Suraini; Molla, Abul H. (Informa UK Limited, 2002)
Bioconversion of higher strength of domestic wastewater biosolids (sludge) (4% w/w of TSS) by mixed fungal culture of Aspergillus niger and Penicillium corylophilum was studied in a laboratory. The effect of potential mixed fungi on domestic wastewater sludge accelerated the liquid state bioconversion (LSB) process. The highest production of dry sludge cake (biosolids) was enriched with fungal biomass to about 85.66g/kg containing 25.23g/kg of protein after 8 days of treatment. The results presented in this study revealed that the reduction of chemical oxygen demand (COD), total suspended solid (TSS), and specific resistance to filtration (SRF) of treated sludge were highly influenced by the fungal culture as compared to control (uninnoculated). The maximum removal rates in treated sludge (biosolids) supernatant recorded were 92% of COD and 98.8% of TSS. Lower SRF (1.08x 1012m/kg) was perceived in microbially treated sludge after 6 days of fermentation. The observed parameters were highly influenced after 8 days of treatment. The influence of pH was also studied and presented in the paper.